2014
DOI: 10.1111/ejn.12723
|View full text |Cite
|
Sign up to set email alerts
|

Complete protection from impending stroke following permanent middle cerebral artery occlusion in awake, behaving rats

Abstract: Using a rodent model of ischemic stroke (permanent middle cerebral artery occlusion; pMCAO), our laboratory has previously demonstrated that sensory-evoked cortical activation via mechanical single whisker stimulation treatment delivered under an anesthetized condition within 2 hours of ischemic onset confers complete protection from impending infarct. There is a limited time window for this protection: rats that received the identical treatment 3 hours following ischemic onset lost neuronal function and susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 64%
“…Such activation results in functional and structural protection from impending ischemic stroke, findings that were independently replicated in other labs. [5][6][7][8][9][10] Further, our findings [11][12][13][14][15][16][17][18] (reviewed in Refs. [19][20][21] have demonstrated that such stimulus-based protection is achievable in anesthetized rats, unrestrained behaving rats, and in old rats.…”
Section: Introductionsupporting
confidence: 64%
“…During acute injury, some regions of the brain sustain immediate hypovolemic damage, while other areas can remain viable and capable of plastic reorganization due to collateral blood flow through pre-existing microcirculation anastomoses. It is this collateral microcirculation that seems to be key to minimizing acute damage and offset adverse outcomes throughout the prolonged period of recovery, and may be accessed by stimulation paradigms like those presented here (Shuaib et al, 2011;Lay et al, 2011Lay et al, , 2012Liebeskind, 2012;Lay and Frostig, 2014). Similarly, chronic sensorimotor recovery is highly dependent on both the activation of existing connections, and the development of new connections either through sensory, motor or combined stimulation (Moskowitz et al, 2010, Nudo andMcNeal, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…urethane or sodium pentobarbital). 1,[30][31][32] Nonetheless, our quantitative analyses of pial arteriole diameter using TPLSM were performed under urethane anesthesia to allow a comparison of vascular effects and degree of neuroprotection observed under isoflurane against a different anesthetic paradigm. While wakefulness and depth of anesthesia alter hemodynamics, the mechanisms of action for urethane spare many pathways involved in neurovascular coupling and recent studies support its use in studies of cerebral hemodynamics.…”
Section: Anesthesia and Monitoringmentioning
confidence: 99%